2017
DOI: 10.1002/jum.14482
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound‐Guided Percutaneous Polidocanol Injection Versus Percutaneous Ethanol Injection for Treatment of Benign Cystic Thyroid Nodules

Abstract: Ultrasound-guided percutaneous polidocanol injection can be an alternative for sclerotherapy of cystic or predominantly cystic thyroid nodules. However, its cost was higher than that of percutaneous ethanol injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 25 publications
1
26
0
5
Order By: Relevance
“…Literature search and characteristics of the included studies A total of 1,772 non-duplicate potentially eligible studies were identified through screening the titles and abstracts, from which 46 articles were retrieved for full text review. The final metaanalysis included 19 studies, consisting of eight two-arm parallel studies (four RCTs [10,11,13,31], two prospective cohort studies [6,32], and two retrospective cohort studies [8,9]), which compared EA with other types of non-surgical management, and 11 single-arm studies ( Fig. 1) [7,12,[33][34][35][36][37][38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Literature search and characteristics of the included studies A total of 1,772 non-duplicate potentially eligible studies were identified through screening the titles and abstracts, from which 46 articles were retrieved for full text review. The final metaanalysis included 19 studies, consisting of eight two-arm parallel studies (four RCTs [10,11,13,31], two prospective cohort studies [6,32], and two retrospective cohort studies [8,9]), which compared EA with other types of non-surgical management, and 11 single-arm studies ( Fig. 1) [7,12,[33][34][35][36][37][38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…Almost all EA procedures described in the included studies involved subtotal or complete aspiration of the fluid content of cystic nodules prior to ethanol instillation. The injected ethanol was either evacuated (aspiration technique) or retained (retention technique) after the procedure in seven [8][9][10][11]13,32,35] and three [31,40,41] studies, respectively. Notably, among studies that enrolled PCTNs, none of them mentioned injection of ethanol into the solid component in addition to filling of the cystic cavity.…”
Section: Characteristics Of the Ablation Techniquesmentioning
confidence: 99%
See 3 more Smart Citations